The Knowledge of Chronic Kidney Disease Risk Among Diabetic Patients at Talise Public Health Center - Windu Unggun Cahya Jalu Putra Windu; Raden Bagus Edy Santoso Nurmalisa; Wirda Wirda; Dina Palayukan Singkali; Asmiwarti Abdullah; Nadya Safira (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Background: Chronic Kidney Disease (CKD) is a serious complication of diabetes mellitus, often leading to end-stage renal failure. Patient knowledge is a critical factor in preventing or slowing its progression. This study aimed to assess the level of knowledge regarding CKD risk among diabetic patients.Methods: A descriptive quantitative study was conducted in the working area of Talise Public Health Center, Palu. From a total population of 219, a sample of 69 respondents was selected using cluster random sampling. Data were collected using a structured questionnaire assessing knowledge of CKD etiology, symptoms, and risk factors. Knowledge levels were categorized as good, sufficient, or poor based on total scores.Results: The study found that less than half of the respondents (37.7%) had good knowledge of CKD risks. A plurality (47.8%) had sufficient knowledge, while 14.5% had poor knowledge.Conclusion: While most diabetic patients in this setting possess at least sufficient knowledge, the proportion with good knowledge remains under 40%. This indicates a significant need for enhanced and targeted patient education programs to improve understanding of CKD risks. Future research should investigate determinants of knowledge and develop effective community-based interventions for CKD prevention.